Pengembangan LKPD Berbasis Lingkungan Sekitar Sebagai Sumber Belajar dalam Pembelajaran Tematik Kelas V SD Negeri 74 Pontianak Barat - Asha Asha; Siti Halidjah; Dyoty Auliya Vilda Ghasha (Journal on Education, 2023)
Student worksheets used in schools only contains evaluation questions and not all subjects use the surrounding environment as a learning resource so that the concepts conveyed are incomplete, so this study aims to develop student worksheets based on the surrounding environment as a learning resource that is feasible according to the results of validation by linguist and material expert. The method used in this research is research and development (R&D) method. The model used in this study refers to Research and Development by Sugiyono. The data sources of this research are linguist validators and material experts. The research instruments used were interview guidelines, linguist validation questionnaires and material expert validation questionnaires. The process of developing student worksheets based on the surrounding environment as a learning resource through 4 stages, namely potential and problems, data collection, product design, and product validation. The level of validation is based on the experts. The linguist obtained an average score of 3,4 with very valid criteria and the percentage value obtained 85% with very feasible information, the material expert obtained an average score of 3,69 with very valid criteria and the percentage result obtained 92,3% with very feasible information